Advances in the pharmacological mechanisms of berberine in the treatment of fibrosis - Liu, Xiaoqin; Liang, Qingzhi; Wang, Yifan; Xiong, Shuai; Yue, Rensong (Frontiers in Pharmacology, 2024)
The rising incidence of fibrosis poses a major threat to global public health, and the continuous exploration of natural products for the effective treatment of fibrotic diseases is crucial. Berberine (BBR), an isoquinoline alkaloid, is widely used clinically for its anti-inflammatory, anti-tumor and anti-fibrotic pharmacological effects. Until now, researchers have worked to explore the mechanisms of BBR for the treatment of fibrosis, and multiple studies have found that BBR attenuates fibrosis through different pathways such as TGF-β/Smad, AMPK, Nrf2, PPAR-γ, NF-κB, and Notch/snail axis. This review describes the anti-fibrotic mechanism of BBR and its derivatives, and the safety evaluation and toxicity studies of BBR. This provides important therapeutic clues and strategies for exploring new drugs for the treatment of fibrosis. Nevertheless, more studies, especially clinical studies, are still needed. We believe that with the continuous implementation of high-quality studies, significant progress will be made in the treatment of fibrosis.